2020
DOI: 10.15252/msb.20209682
|View full text |Cite
|
Sign up to set email alerts
|

A single cell atlas of the human liver tumor microenvironment

Abstract: Malignant cell growth is fueled by interactions between tumor cells and the stromal cells composing the tumor microenvironment. The human liver is a major site of tumors and metastases, but molecular identities and intercellular interactions of different cell types have not been resolved in these pathologies. Here, we apply single cell RNA‐sequencing and spatial analysis of malignant and adjacent non‐malignant liver tissues from five patients with cholangiocarcinoma or liver metastases. We find that stromal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 92 publications
5
114
0
Order By: Relevance
“…A recent sequencing analysis separated CAFs into 3 main subgroups: myofibroblastic CAFs, inflammatory CAFs and antigen-presenting CAFs. Specifically, a recent study revealed recurring, patient-dependent expression programs in stromal cells from primary hepatic duct carcinoma and hepatic metastatic tumors [ 129 , 130 ].…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
“…A recent sequencing analysis separated CAFs into 3 main subgroups: myofibroblastic CAFs, inflammatory CAFs and antigen-presenting CAFs. Specifically, a recent study revealed recurring, patient-dependent expression programs in stromal cells from primary hepatic duct carcinoma and hepatic metastatic tumors [ 129 , 130 ].…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
“…In another study, Massalha et al dissected the spatial distributions of cells in the TMEs using bulk RNA-seq of laser-capture microdissected tissue regions from patients with CCA or liver metastasis. 77 Totally, they collected 63 regions including the tumor core, tumor border, fibrotic region, and tumor islet. Using the cell type-specific gene signatures, they deconvolved the proportions of individual cell types from the bulk measurements of each region.…”
Section: Microenvironmental Reprogrammingmentioning
confidence: 99%
“…The primary approach towards this goal includes multi-dimensional strategies, such as multiplexed morphological methods, including the new imaging mass spectrometry and laser-capture microdissection, or “-omics” technologies, like single cell RNA sequencing. A prime example of the power of such tools applied to the study of the tumor immune microenvironment in human liver malignances is offered by the recent work by Massalha et al [ 46 ]. In this study, the authors analyzed tissue samples from patients who underwent hepatic resection, including three CLM patients, and reconstructed a complete zonation cell atlas of both the malignant and nonmalignant liver, providing a comprehensive analysis of the mechanisms of cross-talk between the tumor microenvironment and carcinomas, and of the tissue spatial gene expression profile.…”
Section: Tissue Immune Parametersmentioning
confidence: 99%